2023
DOI: 10.3390/molecules28196865
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Volatile Components in Dried Fruits and Branch Exudates of Schisandra chinensis with Different Fruit Colors Using GC-IMS Technology

Yiping Yan,
Wenpeng Lu,
Taiping Tian
et al.

Abstract: To investigate the volatile components of Schisandra chinensis (Turcz.) Bail (commonly known as northern Schisandra) of different colors and to explore their similarities and differences, to identify the main flavor substances in the volatile components of the branch exudates of northern schisandra, and finally to establish a fingerprint map of the volatile components of the dried fruits and branch exudates of northern Schisandra of different colors, we used GC-IMS technology to analyze the volatile components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Characteristic VOCs were screened based on VIP > 1.0 and p < 0.05. This screening method has been used in various types of food to select characteristic flavor components [ 30 , 31 , 43 , 44 , 45 ]. In this study, 8 characteristic VOCs were selected from 43 VOCs (as shown in Figure 5 a) in six different cuts of Lueyang black chicken.…”
Section: Resultsmentioning
confidence: 99%
“…Characteristic VOCs were screened based on VIP > 1.0 and p < 0.05. This screening method has been used in various types of food to select characteristic flavor components [ 30 , 31 , 43 , 44 , 45 ]. In this study, 8 characteristic VOCs were selected from 43 VOCs (as shown in Figure 5 a) in six different cuts of Lueyang black chicken.…”
Section: Resultsmentioning
confidence: 99%
“…The differences in volatile flavor substances between samples were assessed, and the results were graphically represented using Origin 2021. We analyze the obtained data using OPLS-DA, OAV values, and VIP values [18].…”
Section: Data Processing and Analysismentioning
confidence: 99%
“…This study uses 'Yanzhihong', a new variety approved by the Institute of Special Products of the Chinese Academy of Agricultural Sciences, as the test material. 'Yanzhihong', a superior Schisandra chinensis variety, exhibits a higher lignan content than the pharmacopeial standard and demonstrates better stress resistance and yield compared to other varieties [17,18]. The study aims to determine its lignans, organic acids, and volatile flavor substances using HPLC and GC-IMS technology, providing a theoretical basis for the optimal harvest time of Schisandra chinensis for various uses and promoting the high-quality development of the industry.…”
Section: Introductionmentioning
confidence: 99%
“…Highly efficient and convenient conditions are provided for the detection of samples that can only be obtained in minute quantities (20). GC-IMS is now used in the fields of foods, odor analysis and environmental testing (21)(22)(23)(24). In addition, GC-IMS technology is used to provide certain theoretical references for the identification, quality evaluation and production of medicinal herbs (25-28).…”
mentioning
confidence: 99%